Physiological and Perceptual Responses to Self-Selected Exercise Pace on A Track Versus Treadmill - Riley Galloway, Ph.D; Robert Booker, M.S; Hunter Haynes, M.S; Megan Holmes, Ph.D; Jacob Gdovin, Ph.D (International Universities Strength and Conditioning Association, 2021)
Objective: To investigate differences between a controlled and non-controlled exercise modality when walking and running at self-selected pace. Methods: Male and female participants (N=30, 21.07±0.88 years of age) engaged in four sessions testing V̇O2max, one-mile walk and run on an indoor track, and one-mile walk and run on a laboratory treadmill. With a significance level set at p £ 0.05, the following results were found. Results: Walking and running heart rate and rating of perceived exertion were significantly higher on the treadmill compared to the track (p<0.05). However, energy expenditure showed no significant difference between exercise modality (p=0.611). Treadmill exercise resulted in higher V̇O2 values for males during both walk and run pace (p=0.041 and p=0.002, respectively). Conclusions: Exercise programming is an individualized process which should consider differences among modalities, settings, and affective responses. We observed an increased perceived effort during treadmill exercise while maintaining similar energy expenditure. The provisions of autonomy and individuality may decrease perceived effort while maintaining energy expenditure, thus providing positive affective responses promoting adherence. With these differences between modalities in mind, exercise professionals should consider appropriate adjustments to intensity when targeting specific adaptations. These adjustments may also influence adherence to a prescribed program.